PENCEMARAN LIMBAH PLASTIK DAN UPAYA PENGELOLAAN LINGKUNGAN BERKELANJUTAN DI KOTA PEKANBARU - Farhan Sidiq Hartanto (Pelantar Press, 2025)
The purpose of this study is to determine the impact of plastic waste pollution on the environment and its mitigation efforts in Pekanbaru. This study was conducted using qualitative methods supported by reference sources and literature, both books, research results and national and international scientific journals. From the results of this study, it was found that plastic waste can have a very large impact on the environment. Even plastic materials that enter the environment as plastic waste will not be decomposed in the near future. The types of plastic waste in the form of filaments that are commonly found from observations are plastic bags, used plastic bottles for drinks, plastic wrappers and food and beverage packaging and sachet waste. When ingested by humans through fish, shellfish, and water, the toxic pollutant materials will move into the human body and cause hormonal disturbances. The mitigation efforts that can be done include prioritizing waste management, especially plastic waste through efforts to encourage the Pekanbaru City government to control water and land pollution by prioritizing controlling the use of single-use plastics and handling plastic waste. Then the need for efforts to support the sorting and processing of organic waste. Plastic waste is also used for handicrafts and others which are hygienic and have economic value and are beneficial to the community. This is a kind of sustainable environmental management